👤
a fost răspuns

Vă rog! ! ! ! ! ! ! ! ! ! ! ! ! !

Vă Rog class=

Răspuns :

Mikkka

Am atasat rezolvarea

Vezi imaginea Mikkka

[tex]\it x=\left(-\dfrac{5}{12}+\dfrac{^{2)}1}{\ 6}\right)+\left(-\dfrac{1}{18}-\dfrac{^{2)}4}{\ 9}\right) =\dfrac{-5+2}{12}+\dfrac{-1-8}{18} =\dfrac{-3^{(3}}{12}-\dfrac{\ 9^{(9}}{18}=\\\\=\dfrac{-1}{4}-\dfrac{^{2)}1}{2}=\dfrac{-1-2}{4} = -\dfrac{3}{4}[/tex]

[tex]\it y = \left(- \dfrac{^{2)}3}{10} +\dfrac{7}{20} \right) + \left(-\dfrac{^{2)}4}{\ 15} -\dfrac{^{5)}1}{\ 6} \right) = \dfrac{-6+7}{20} +\dfrac{8-5}{30}=\\\\=\dfrac{1}{20}+\dfrac{\ 3^{(3}}{30}=\dfrac{1}{20}+\dfrac{^{2)}1}{10}=\dfrac{1+2}{20}=\dfrac{3}{20}[/tex]


[tex]\it x+y=-\dfrac{^{5)}3}{\ 4}+\dfrac{3}{20} =\dfrac{-15+3}{20}= \dfrac{\ -12^{(4}}{20} = -\dfrac{3}{5}[/tex]